2023
DOI: 10.1039/d3ob00732d
|View full text |Cite
|
Sign up to set email alerts
|

NHC-catalyzed formal [3 + 3] annulations of δ-acetoxy allenoates for the synthesis of 4H-pyran derivatives

Abstract: Herein, an N-heterocyclic carbene (NHC) catalyzed formal [3+3] annulation of δ-acetoxy allenoates with 1C,3O-bisnucleophiles for the construction of 4H-pyrans has been developed. This protocol provides a facile mothod to synthesize...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Henceforth, Lewis bases catalyzed divergent annulations of δ-acetoxy allenoate have been reported and developed (Scheme a) . Very recently, our research group found that N-Heterocyclic Carbene (NHC) could also catalyze the [3 + 3] cycloaddition reaction of δ-acetoxy allenoates with 1C,3O-bisnucleophiles . Additionally, Tong and co-workers reported thermal promoted [3 + 2] cycloadditions of δ-acetoxy allenoates with various 1,3-dipoles including azomethine imines, nitrones, and azomethine ylides, affording 2,3-dihydropyrazoles, 2,3-dihydroisoxazoles, and indolizines, respectively (Scheme b) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Henceforth, Lewis bases catalyzed divergent annulations of δ-acetoxy allenoate have been reported and developed (Scheme a) . Very recently, our research group found that N-Heterocyclic Carbene (NHC) could also catalyze the [3 + 3] cycloaddition reaction of δ-acetoxy allenoates with 1C,3O-bisnucleophiles . Additionally, Tong and co-workers reported thermal promoted [3 + 2] cycloadditions of δ-acetoxy allenoates with various 1,3-dipoles including azomethine imines, nitrones, and azomethine ylides, affording 2,3-dihydropyrazoles, 2,3-dihydroisoxazoles, and indolizines, respectively (Scheme b) .…”
mentioning
confidence: 99%
“…5 Very recently, our research group found that N-Heterocyclic Carbene (NHC) could also catalyze the 3] cycloaddition reaction of δ-acetoxy allenoates with 1C,3Obisnucleophiles. 6 Additionally, Tong and co-workers reported thermal promoted [3 + 2] cycloadditions of δ-acetoxy allenoates with various 1,3-dipoles including azomethine imines, nitrones, and azomethine ylides, affording 2,3dihydropyrazoles, 2,3-dihydroisoxazoles, and indolizines, respectively (Scheme 2b). 7 Inspired by the aforementioned and our group's work on the transformations of functionalized allenoates facilitated by NHC, we envisioned that NHC should push forward the reaction of hydroxylamines and δ-acetoxy allenoates.…”
mentioning
confidence: 99%